Intracranial Pressure During the Development of Renovascular Hypertension - Fernandes, Marcos Vinicius [UNESP]; Melo, Mariana Rosso [UNESP]; Mowry, Francesca Elisabeth; Lucera, Gabriela Maria [UNESP]; Lauar, Mariana Ruiz [UNESP]; Frigieri, Gustavo [UNESP]; Biancardi, Vinicia Campana; Menani, Jose [UNESP]; Almeida Colombari, Debora Simoes [UNESP]; Colombari, Eduardo [UNESP] (Lippincott Williams & Wilkins, 2021)
The mechanisms by which changes in intracranial pressure (ICP) occur during hypertension are unclear. The experimental 2K1C (2-kidney, 1-clip) hypertension is a model characterized by sympathetic and renin-angiotensin system overactivation in which ICP still needs investigation. In the present study, we analyzed ICP alterations during the development of 2K1C hypertension using invasive and noninvasive ICP recording methods. We also tested the importance of AT1R (angiotensin II type 1 receptor) activation for the ICP changes and investigated the integrity of the blood-brain barrier within central cardioregulatory nuclei in 2K1C hypertensive rats. 2K1C hypertension was induced in 6-week-old male rats (150 g). In the fourth week of 2K1C hypertension induction, when mean arterial pressure reached 162 +/- 2 mm Hg, ICP significantly increased, ICP pulse waveforms changed, increasing the ratio between the two peaks (P2/P1 ratio) of the ICP waveform. In the third week of 2K1C hypertension induction, blood-brain barrier disruption was detected within the hypothalamic paraventricular nucleus, rostral ventrolateral medulla, and nucleus tractus solitarius. In the sixth week, intravenous losartan (AT1R antagonist) or the vasodilator hydralazine acutely reduced arterial pressure to normotensive levels. Losartan, but not hydralazine, partially reduced the increase of ICP and P2/P1 ratio in hypertensive rats. These results show significant changes in ICP in 2K1C hypertensive rats and suggest that AT1R activation may contribute to elevated ICP during hypertension-an effect possibly intensified by the blood-brain barrier disruption in important central cardioregulatory nuclei in renovascular hypertensive animals.
Keywords: angiotensin II; arterial pressure; hypertension; intracranial pressure; losartan